Blades and methods for manufacturing blades
Patent Information
- Application Number
- JP2022179792
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-11-09
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2042-11-09
AI Technical Summary
【0015】 本発明によれば、潤滑コーティング層がアンカー効果を得ることができるので、潤滑コーティング層を剥がれ難くすることで切断品質を向上させることが可能である。
Smart Images

Figure 0007933636000003 
Figure 0007933636000004 
Figure 0007933636000005
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to a cutter used for various types of cutting, in particular, a cutter suitable for a replaceable microtome blade that slices a sample such as a tissue embedded in paraffin into extremely thin sections, and a method for manufacturing the same.
BACKGROUND ART
[0002] In recent years, the cutting quality required for cutters has evolved beyond the stage of merely being able to separate a workpiece, and for processing applications such as microtomes, electronic component materials, and semiconductor materials, cutters capable of high-quality cutting with no damage to the cut surface or skewed cutting at high cutting speeds have come to be demanded. To meet such demands, lubricious coating treatments and the like have been performed for the purpose of reducing the frictional resistance of the blade surface, allowing the blade surface to slide after cutting and promoting separation of the cut workpiece.
[0003] As techniques related to reducing frictional resistance during such cutting, those described in Patent Documents 1 to 4 are known. Patent Document 1 describes a kitchen knife in which a fluororesin layer is baked and coated on a portion of the cutter. Further, Patent Documents 2 to 4 also describe forming a resin-based coating layer as a lubricating coating layer for the purpose of reducing friction during cutting.
PRIOR ART DOCUMENTS
PATENT DOCUMENTS
[0004]
PATENT DOCUMENT 1
PATENT DOCUMENT 2
PATENT DOCUMENT 3
PATENT DOCUMENT 4
[0005] In the prior art described above (Patent Documents 1-4), a lubricating coating layer is formed on the blade, which reduces frictional resistance on the blade surface and promotes the delamination of the cut material after cutting. However, as cutting is repeated, the lubricating coating layer peels off. When this happens, scratches occur on the cut surface of the cut material, and the cut material adheres to the blade surface and the edges where the coating layer has peeled off, resulting in a significant decrease in cutting quality.
[0006] Therefore, the present invention aims to provide a cutting tool and a method for manufacturing a cutting tool that have a longer lifespan and superior cutting quality than conventional products by forming a peel-resistant lubricating coating layer on a cemented carbide alloy. [Means for solving the problem]
[0007] The blade of the present invention is made of a cemented carbide alloy consisting of metal particles and a binder, and has a blade body having a flat base and a pointed portion formed at the tip of the base, and has a blade body having irregularities on at least the surface of the pointed portion, with the ground metal particles forming convex portions and the binder forming concave portions, and has a lubricating coating layer formed on at least the pointed portion by solidifying a liquid coating material.
[0008] The present invention relates to a method for manufacturing a cutting tool, comprising a cutting tool body made of a cemented carbide alloy consisting of metal particles and a binder, having a flat base and a pointed portion formed at the tip of the base, wherein a liquid coating material is applied to at least the pointed portion of the cutting tool body, which has an uneven surface with ground metal particles forming convex portions and the binder forming concave portions, and solidified to form a lubricating coating layer.
[0009] In the blade of the present invention, at least the pointed surface has irregularities, with the ground metal particles forming convex portions and the binder forming concave portions. When a lubricating coating layer is formed on at least the pointed portion of the blade body, the total surface area of the blade body increases due to the irregularities, and an anchoring effect can be obtained as the coating material penetrates and solidifies in the concave portions, making it difficult for the lubricating coating layer to peel off.
[0010] In particular, blades used as microtome blades are required to slice samples such as cell tissue embedded in paraffin into extremely thin sections ranging from micrometers to tens of nanometers in thickness. Therefore, the thickness of the lubricating coating layer must also be tens of nanometers. The blades of the present invention make it possible to prevent peeling even with such an extremely thin lubricating coating layer.
[0011] The cemented carbide is preferably a composite material obtained by sintering metal particles with a particle size of 0.7 μm or less with 10% to 16% by mass of a binder. The smaller the particle size of the metal particles and the larger the amount of binder, the more likely the surface of the cutting tool body will become uneven after grinding. The uneven surface allows for a larger coating area, and the coating material penetrates into the depressions, increasing the adhesion strength of the coating and making it less likely to peel off. On the other hand, with metal particles larger than 0.7 μm, the surface irregularities become less pronounced because the particles are too large. Since smaller particle sizes increase costs, the lower limit of the acceptable particle size is determined based on the intended use of the cutting tool. Regarding the binder content, materials sintered with less than 10% by mass of binder may have a low binder content, resulting in less surface roughness and potentially failing to achieve sufficient coating adhesion strength. Furthermore, increasing the binder percentage reduces wear resistance and shortens the lifespan of the cutting tool. Therefore, a binder content of 10% to 16% by mass is desirable.
[0012] The lubricating coating layer is formed from a primer layer and a topcoat layer, and the topcoat layer may be formed from a monolayer. Because the topcoat layer of the lubricating coating layer is formed from a monolayer, it can be made thinner than a topcoat layer formed by multiple overlapping topcoat particles.
[0013] The pointed portion comprises a first region extending from the cutting edge tip, including the tip of the cutting edge, and a second region following the first region, wherein the primer layer of the first region may be formed to be thinner than the primer layer of the second region. By forming a thinner primer layer in the first region than in the second region, and then depositing a monolayer topcoat on the primer layer, it is possible to ensure a thin first lubricating coating layer in the first region. Therefore, it is possible to reduce stresses such as friction applied during cutting without compromising the cutting performance from the cutting edge to the first region.
[0014] The surface roughness of the cutting tool surface in the first region can be made smoother than that of the cutting tool surface in the second region. Since the coating material forming the primer layer in the first region is attracted to the surface tension of the coating material on the blade surface in the second region and moves to the second region, the primer layer in the first region can be made thinner than the primer layer in the second region. [Effects of the Invention]
[0015] According to the present invention, the lubricating coating layer can achieve an anchoring effect, making it difficult for the lubricating coating layer to peel off and thereby improving cutting quality. [Brief explanation of the drawing]
[0016] [Figure 1] These are diagrams of a blade according to an embodiment of the present invention, where (A) is a diagram showing the entire blade and (B) is a diagram showing a magnified portion of the blade. [Figure 2A]This is a diagram partially omitting the tip end portion of the blade shown in Figure 1. [Figure 2B] This diagram partially omits the tip end portion of the blade shown in Figure 1, and shows the radius of curvature and the included edge angle (edge tip angle). [Figure 3] This is a diagram for explaining the rake angle and clearance angle of the blade shown in Figure 1. [Figure 4] This is a schematic diagram partially omitting the first region, the second region, and the third region of the blade shown in Figure 1. [Figure 5] This is an enlarged cross-sectional view of the surface of the blade main body. [Figure 6] This is a diagram for explaining the movement of the replacement blade for a microtome used in the examples, where (A) is a view seen from above, and (B) is a view seen from the side. [Figure 7] (A) is a diagram showing a micrograph of the vicinity of the tip of the blade main body before coating of a blade made of a cemented carbide with a WC grain size of 1.5 μm and a Co content of 5 wt%, and (B) is a diagram showing a micrograph of the vicinity of the tip of the blade main body before coating of a blade made of a cemented carbide with a WC grain size of 0.7 μm and a Co content of 12 wt%. [Mode for Carrying Out the Invention]
[0017] The blade according to the embodiment of the present invention will be described based on the drawings. Figure 1 is a view of the entire blade according to the embodiment of the present invention and a partially enlarged view showing the blade, Figure 2A is a diagram partially omitting the tip end portion of the blade shown in Figure 1, Figure 2B is a diagram partially omitting the tip end portion of the blade shown in Figure 1 and showing the radius of curvature and the included edge angle (edge tip angle), Figure 3 is a diagram for explaining the rake angle and clearance angle of the blade shown in Figure 1, and Figure 4 is a diagram partially omitting the first to third regions of the blade shown in Figure 1, where the middle portion is omitted at the position indicated by the wavy line in order to show the whole while displaying the coating particles.
[0018] As shown in Figure 1, the blade 10 according to an embodiment of the present invention is made of cemented carbide and is a flat blade with a straight cutting edge. The blade 10 is used as a microtome replacement blade for a microtome to slice a sample, such as cell tissue embedded in paraffin, to an extremely thin thickness of tens of nanometers (for example, about 2 μm) to form sections. The blade body 1 of the blade 10 is formed with a blade length L of approximately 80 mm, a thickness t of approximately 0.25 mm, and a width W of approximately 8 mm. The blade body 1 comprises a base 1A with a width W1 of approximately 7.3 mm and a pointed portion 1B formed from the base 1A to the tip with a width W2 of approximately 0.7 mm.
[0019] The ends of the cutting edge of the blade body 1 are processed (chamfered) with triangular cutouts called C-beams. In this embodiment, the four corners are processed with C-beams. The C-beams are formed by cutting out isosceles triangles with sides of approximately 2 mm. The blade body 1 has a blade length L of approximately 80 mm, and when cutting a material (for example, a thin section) with a width of approximately 30 mm, even when a 45° shear angle is applied with a sliding microtome, the length is only about 42 mm, which is 1 / cos45° (1.4114) times that length. Therefore, the four corners of the blade 10, where chamfers are formed, are not cut.
[0020] The pointed portion 1B is formed in a tapered shape, gradually becoming narrower from the base portion 1A. As shown in Figures 2A and 3, the cutting edge E of the pointed portion 1B is formed with a sharpness angle (cutting edge angle) θ of 18 to 22 degrees and a radius of curvature R of the cutting edge tip of 20 nm to 40 nm. Here, the sharpness angle θ is the angle that forms the cutting edge tip E (cutting edge angle), and represents the angle at the intersection formed when the cutting surfaces (blade surfaces) on both the front and back sides of the pointed portion 1B are extended. A smaller sharpness angle θ improves cutting quality, but it also increases the likelihood of chipping, shortening the lifespan. Conversely, if the sharpness angle θ is too large, cutting quality deteriorates. When the cell tissue embedded in paraffin is from common organs such as the kidneys, heart, liver, lungs, and brain, the sharpness angle θ is desirable to be between 18 and 22 degrees, even considering the shear angle of the sliding microtome. A smaller radius of curvature R at the tip of the blade improves cutting quality because the blade becomes sharper, but it also shortens the lifespan because chipping is more likely to occur. Conversely, a larger radius of curvature R at the tip of the blade reduces cutting quality. For common organs such as kidneys, hearts, livers, lungs, and brains, a radius of curvature R at the tip of the blade is desirable between 20 nm and 40 nm. As shown in Figure 2B, the shape of the tip of the blade may also be such that the pointed part 1B curves from a straight line to the tip of the blade E, and in this case, the radius of curvature R and the pointed angle (tip angle) θ of the blade are as shown in the figure.
[0021] As shown in Figure 3, the relief angle β1, which is the angle between the reference line H, which is parallel to the direction in which the cutting tool moves (cutting direction), and the relief face 12, can be 10° to 20°. Therefore, when the sharpness angle is 20°, the rake angle β2, which is the angle between the reference line V, which is perpendicular to the direction in which the cutting tool moves, and the rake face 11, can be 60° to 50° (β2 = 90° - β1 - θ).
[0022] As shown in Figure 4, the pointed portion 1B includes a first region A1 extending from the cutting edge tip E, which includes the cutting edge tip E, and a second region A2 that follows the first region A1 and is wider than the first region A1. The base portion 1A also includes a third region A3. The first area A1 is polished to a mirror finish, and then polished to a surface roughness level of Ra 0.002. The second area A2 is finished to an Ra level of 0.02. The third area A3 is also finished to an Ra level of 0.2. Therefore, the surface roughness Ra in the first region A1 is formed to be smoother than that in the second region A2, and the surface is finished in such a way that the relationship is first region A1 < second region A2 < third region A3.
[0023] A lubricating coating layer C is formed in the first region A1 to the third region A3. A first lubricating coating layer C1 is formed in the first region A1. For example, when preparing thin cell sections from a hard, paraffin-embedded specimen using a microtome, images captured with a high-speed camera showed that paraffin adhered to the area up to approximately 1 μm from the blade tip E. Furthermore, the wear condition of the blade tip during cutting confirmed that the first region A1, which contributes to the cutting, extended from at least 1 μm to 20 μm from the blade tip E.
[0024] The first lubricating coating layer C1 is formed so that its thickness is uniform from the cutting edge tip E toward the second region A2. The thickness of the first lubricating coating layer C1 is approximately 15 nm.
[0025] The range of the second region A2, which is continuous with the first region A1, can be, for example, approximately 700 μm from the cutting edge tip E. In the second region A2, a second lubricating coating layer C2 is formed extending from the boundary with the first region A1 toward the third region A3. The thickness of the second lubricating coating layer C2 is formed to be approximately 20 nm.
[0026] The third region A3 following the second region A2 can, for example, encompass the entire base 1A. The third region A3 is formed to have a thickness equivalent to or approximately 25 nm of the second lubricating coating layer C2. Thus, the lubricating coating layer C is formed with a thickness of 15 nm to 25 nm, with the thickness increasing in stages from the first lubricating coating layer C1 to the third lubricating coating layer C3. In the case of microtome replacement blades, the thickness of the lubricating coating is 10 nm to 30 nm.
[0027] The lubricating coating layer C formed on the base portion 1A and the pointed portion 1B is created by coating the surfaces of the base portion 1A and the pointed portion 1B with primer particles 2 (see Figure 2A) that form the first layer (primer layer L1) and topcoat particles 3 (see Figure 2A) that form the second layer (topcoat layer L2, water-repellent coating layer).
[0028] In the first region A1, a first lubricating coating layer C1 with a coating layer thickness of approximately 15 nm is formed by the primer particles 2 and topcoat particles 3. The thickness of the first lubricating coating layer C1 must be approximately 15 nm, including the primer particles 2 and topcoat particles 3, while maintaining the relationship "primer particles < topcoat particles". Generally, commercially available inorganic (silica) ultrafine particles have progressively larger particle sizes starting from 5 nm, and it is important to create a combination of particle sizes that satisfies the above conditions. The reason for making the particle size of topcoat particles 3 larger than that of primer particles 2 is that it increases the surface irregularities of the topcoat layer L2, which functions as a water-repellent coating layer, thus improving water repellency.
[0029] On top of the primer layer L1, the topcoat layer L2 is formed by inorganic irregularities created by topcoat particles 3, and fluorine adheres to the topcoat particles 3 like cilia, thus forming a coating layer similar to the lotus effect. The topcoat layer L2 is formed by a monomolecular film in which topcoat particles 3 are arranged in a two-dimensional single layer. This allows the shape of the pointed portion 1B to be faithfully reproduced without the lubricating coating layer C becoming thicker and duller, thus maintaining sharpness.
[0030] The primer layer L1 consists of inorganic fine particles and anionic surfactants such as fatty acid salts, amino groups, alkylbenzene sulfonates, special polycarboxylic acid-type polymer surfactants, and naphthalene sulfonate formalin condensates, selected to best suit the superhard material (substrate). The optimal material was determined based on surface activity energy and contact angle, and by using it, the water contact angle of the topcoat liquid was approximately 5°.
[0031] The lubricating coating layer C basically uses a fluorine-based water-repellent coating material, but the coating material is formulated and used so that the water contact angle is approximately 110° or higher. Furthermore, it is important to ensure a surface roughness that does not cause scratches or damage to the object being contacted. After the composition is coated and dried, the surface irregularities caused by fine particles are kept to approximately 15 nm in the case of the first region A1.
[0032] For the material used for the cutting tool, a cemented carbide alloy with a tungsten carbide (WC) particle size of 0.7 μm or less was used to create an uneven surface on the cutting tool body after grinding, which prevents the coating from peeling off easily.
[0033] Here, particle size refers to the average particle size measured by the Sub-Sieve Sizer method. The average particle size using the Sub-Sieve Sizer method is calculated by passing air through the sample, measuring the flow velocity and pressure drop, determining the specific surface area, and then calculating the particle size. The Fischer method and the Blaine method can be used for the permeation method.
[0034] Because the grain size of WC is larger than the diameter of the radius of curvature R at the tip of the cutting edge, the WC must be cut away. It is important that the cutting stress at that time is less than the bonding force between the WC and Co. If the cutting stress is greater than the bonding force, the WC particles will peel off, and the cutting surface will appear to chip. In terms of strength, a cemented carbide material with a hardness of 90 (HRC) or higher, a flexural strength of 3.0 GPa to 4.0 GPa, and a Young's modulus of around 570 GPa is desirable.
[0035] Furthermore, the blade thickness t shown in Figure 1 can be set to 0.1 mm for processing electronic component materials, and to 0.25 mm for pathological purposes to collect thin section specimens. Here, blade thickness t refers to the thickness of the base portion 1A in the area that penetrates the object to be cut during cutting. If the thickness of the flat base portion 1A is not uniform, it refers to the thickness of the base in the area closer to the pointed portion 1B.
[0036] Here, we will describe the cemented carbide that forms the blade body 1. Figure 5 is an enlarged cross-sectional view of the surface of the blade body. Hard metals (hard metals, cemented carbide) are composite materials made by sintering metal particles consisting of carbides of metals from groups IVa, Va, and VIa of the periodic table with a binder of iron-based metals such as Fe, Co, and Ni. Of these composite materials, WC-Co alloys have the best mechanical properties and are often referred to as cemented carbide. In addition to WC-Co alloys, WC-TiC-Co, WC-TaC-Co, and WC-TiC-TaC-Co alloys, which have improved oxidation resistance, are sometimes used as cutting tools. Furthermore, cemented carbide with Ni as the binder loses its magnetism and becomes non-ferromagnetic when the amount of W solid solution in Ni exceeds a certain level, and WC-Ni alloys have been put into practical use due to their improved corrosion resistance, as have WC-Ni-Cr alloys, which have improved corrosion resistance due to the addition of Cr.
[0037] Furthermore, in the case of cemented carbide made of WC-Co material, the binder Co is softer than the metal particles WC. Therefore, when the cemented carbide material is ground into the shape of the cutting tool body 1, as shown in Figure 5, the Co portion 14 tends to become concave relative to the ground and flattened WC portion 13. In other words, the Co portion 14, which is the binder, becomes a recess 16 relative to the ground WC surface, resulting in irregularities 17 on the surface.
[0038] Next, a grinding method for forming irregularities 17 on the surface of the blade body 1 will be described. Because cemented carbide is a difficult material to machine, diamond wheels are often used for grinding. Generally, rough machining is performed with a grinding wheel with a large abrasive particle size (small grit number), and finishing is performed with a grinding wheel with a small abrasive particle size (large grit number). When finishing grinding is performed with a high-grit whetstone, the surface of the blade body 1 can be made mirror-like, and in this case, both the WC portion and the Co portion are ground to almost the same surface. If a grinding wheel with a slightly lower grit than the one used at this time is used, the amount of abrasive grain protrusions on the surface of the grinding wheel is larger, so as shown in Figure 5, the softer Co portion 14 is ground more than the WC portion 13, and convex portions 15 made of ground WC and concave portions 16 made of Co are formed on the surface of the blade body 1. This makes it possible to form an uneven surface 17 that is suitable for applying a coating that is less likely to peel off. Regarding the formation of irregularities on the surface of the blade body 1, other methods are also possible, such as using a liquid polishing agent containing free diamond abrasive particles to accelerate the removal of the Co portion and create larger irregularities on the surface of the blade body 1, or forming recesses in the Co portion through blasting or chemical treatment.
[0039] In the cutting tool 10 according to this embodiment, the cutting tool body 1 is formed by grinding a cemented carbide material, and a lubricating coating layer C is formed on the cutting tool body 1 by solidifying a liquid coating material. By doing so, the total surface area of the grinding surface itself is increased, and the coating material penetrates into the recesses 16, making it easier for the coating material to adhere and providing an anchoring effect when it hardens. Therefore, when the workpiece is cut by the blade 10, peeling of the lubricating coating layer C that comes into contact with the workpiece can be suppressed, improving the durability of the lubricating coating layer C, and thus improving the cutting quality.
[0040] Thus, in the cutting tool 10, the first lubrication coating layer C1 to the third lubrication coating layer C3 shown in Figure 4 are formed with recesses 16 between the ground WC particles (WC portion 13). Note that the arrangement of primer particles shown in Figure 4 is just one example.
[0041] Next, a method for manufacturing a blade coated with the above-described example will be explained. A known dipping method was used to apply a thin coating to the tip E of the blade. Taking advantage of the characteristics of dipping coating, the blade tip (pointed part 1B) was positioned on the longitudinal side (vertical direction) and dipped into the liquid coating material in the longitudinal direction. For the primer layer (first layer), the basic principle is to apply a thin coating. The faster the lifting speed, the thicker the coating layer becomes, and the slower the lifting speed, the thinner it becomes. Therefore, taking advantage of the property that the primer layer (first layer) becomes thinner when lifted slowly, the lifting speed is set to 0.25 mm / s to 0.5 mm / s for application. After coating the primer layer, the topcoat layer (second layer) was applied at a speed of 10 mm / s to 20 mm / s to form a monolayer film.
[0042] As a result, a primer layer L1 with a thickness of approximately 5 nm is formed in a first region A1 10 μm from the tip of the blade E, and a primer layer L1 with a thickness of approximately 10 nm or more is continuously formed in a second region A2 following the first region. Furthermore, a primer layer L1 with a thickness of approximately 15 nm or more is continuously formed in a third region A3 following the second region A2.
[0043] This is because the cutting edge is located on the longitudinal side, the blade surface of the first region A1 is extremely smooth and has a mirror finish, the blade surface of the second region A2 is rougher than that of the first region A1, and the blade surface of the third region A3 is rougher than that of the second region A2.
[0044] Therefore, the coating material forming the primer layer L1 on the first region A1 is attracted by the surface tension of the coating material on the blade surface in the second region A2 and moves to the second region, making it possible to make the first lubricating coating layer C1 thinner than the second lubricating coating layer C2 at the pointed portion 1B. Similarly, the second coating layer C2 can be formed thinner than the third lubricating coating layer C3.
[0045] In this way, by forming the primer layer L1 uniformly in the first region A1 and thinner than the second region A2, and then depositing a monolayer topcoat layer L2 on the primer layer L1, the thickness of the first lubricating coating layer C1 in the first region A1 can be kept thin. This reduces stress such as friction applied during cutting without compromising the cutting performance from the blade tip E to the first region A1. Furthermore, since the primer layer L1 in the second region A2 is thicker than that in the first region A1, the topcoat layer L2 can be firmly fixed, thereby increasing the durability of the topcoat layer L2.
[0046] As shown in Figure 1, the corners of the blade 10, including the pointed portion 1B, are machined with a chamfer. Therefore, the coating liquid adhering to the end of the pointed portion 1B located at the lower end flows from the pointed portion 1B along the chamfer to the base portion 1A. Consequently, even though a chamfer is formed at the tip of the blade, it does not affect cutting as it is a non-cutting portion, and it is possible to prevent the coating liquid from accumulating and hardening at the pointed portion 1B. Thus, it is possible to prevent the first or second lubricating coating layer at the pointed portion 1B located at the lower end from becoming too thick.
[0047] In this embodiment, the four corners are chamfered, but since liquid accumulation may not cause problems during cutting or installation, the corners of the base 1A can be left chamfered, and only the ends of the cutting edge can be chamfered. Also, since the cutting tool is a part made by grinding, the edges are sharp and there is a risk of injury, which is one of the reasons for chamfering.
[0048] Furthermore, the blade 10 has chamfered edges on the corners of the base 1A opposite the pointed portion 1B. Therefore, it is possible to prevent uneven distribution of the coating liquid between the pointed portion 1B and the base 1A, allowing the coating liquid to drip uniformly and be easily removed.
[0049] In the above description of the manufacturing method, the lubricating coating layer was formed by the dipping method. However, since the topcoat layer is formed of a monomolecular film, even if it adheres thickly to the blade 10, the topcoat particles that overlap the topcoat particles arranged in a two-dimensional single layer will peel off during rinsing after after-baking. Therefore, the lubricating coating layer can be applied by methods other than the dipping method, such as spray application or brush application.
[0050] [Example 1] The cutting tools according to the above embodiment were made from cemented carbide with different WC particle sizes and Co content, and the durability of the lubricating coating layer was tested (life test) by cutting a workpiece. Four conditions were used for the WC particle size: 0.3 μm, 0.5 μm, 0.7 μm, and 1.5 μm, and six conditions were used for the Co content: 5 wt%, 6 wt%, 10 wt%, 12 wt%, 14 wt%, and 16 wt%.
[0051] As shown in Figure 6(A), the life test was performed using a sliding microtome in which the cutting edge of a blade attached to a holder (not shown) was positioned at a predetermined angle (in this embodiment, α was set to 45°) with respect to the reference line L11, and the blade was moved back and forth in a direction perpendicular to the reference line L11 to slice the material to be cut into sections. The cutting edge is inclined relative to the reference line L11, and as the workpiece moves back and forth in a direction perpendicular to the reference line L11, the initial position where the cutting edge strikes the workpiece remains the same. Marking lines were added in the width direction so that when the cutting tool is removed and reattached, it will be in the same position on the workpiece as it was initially. Furthermore, as shown in Figure 6(B), the relief angle β1, which is the angle between the reference line H parallel to the direction of the cutting tool's movement and the relief face 12, is 16.4°. Also, the rake angle β2, which is the angle between the reference line V perpendicular to the direction of the cutting tool's movement and the rake face 11, is 53.6°.
[0052] This cutting tool uses the cutting tool 10 shown in Figure 1. Therefore, the blade length L is approximately 80 mm, the thickness t is approximately 0.25 mm, and the width W is approximately 8 mm. In addition, the width W1 is approximately 7.3 mm and the width W2 is approximately 0.7 mm, and the tip angle (blade edge angle) is 20°. One end of the blade 10 is marked with a mark M (see Figure 6(A)) to distinguish between the front and back sides. All of the cutting tools are replacement microtome blades, with the same lubrication coating layers (first lubrication coating layer C1 to third lubrication coating layer C3 (see Figure 4)) prepared under the same processing / coating conditions.
[0053] The samples used were sections of pig cell tissue (kidney, heart, liver, lung, and brain) embedded in paraffin. Furthermore, the embedded samples were prepared with a uniform size of tissue whenever possible. The lifespan test involves repeatedly cutting each of the implanted specimens—kidney, heart, liver, lungs, and brain—20 times in that order, obtaining 20 sections. If there are no problems with the quality of the sections, the process is repeated again, starting with the kidney. The thickness of all thinly sliced sections was set to 2 μm. Even when the machine was set to a thickness of 2 μm, there were times when the section became thicker and the machine could no longer cut properly; however, these cases were also counted as one instance.
[0054] The quality of the sections was assessed by scooping thin sections onto a glass slide, staining them, and observing them under a 40x optical microscope. Sections without scratches, tears, or other scalpel marks were considered acceptable. A digital microscope VHX-7000 (100x) was used. Note that any microscope with a magnification of 40x or higher can be used. Furthermore, the area shrinkage rate of the thinly sectioned material compared to the original sample was checked. When sectioning, if the sliding properties between the section and the cutting tool are poor, the area of the section will shrink. Less area shrinkage is desirable. A shrinkage rate of ((section area) / (original sample area)×100) of 70% or more was considered acceptable. Ultimately, only materials that passed the cutting quality test after more than 2000 cutting cycles in both scalpel wound and shrinkage rate were deemed to meet the quality standards.
[0055] Table 1 shows the results of evaluating the cutting quality of microtome blades that were processed and coated using cemented carbide alloys with different WC grain sizes and Co content.
[0056] [Table 1]
[0057] We confirmed that the cutting quality of microtome blades, which were processed and coated using cemented carbide with a WC particle size of 0.7 μm or less and a Co content of 10-16 wt%, reached the target cutting quality.
[0058] Figure 7(A) shows a micrograph of the area near the tip of a cutting tool before coating, made from cemented carbide with a WC grain size of 1.5 μm and a Co content of 5 wt%. Figure 7(B) shows a micrograph of the area near the tip of a cutting tool before coating, made from cemented carbide with a WC grain size of 0.7 μm and a Co content of 12 wt%. The cutting quality of the blade made from cemented carbide with a WC particle size of 1.5 μm and a Co content of 5 wt% was unacceptable. However, as shown in Figure 7(A), the blade body before coating had few irregularities on its surface, suggesting that the anchoring effect of the coating material was low. The cutting quality of the blade made from cemented carbide with a WC particle size of 0.7 μm and a Co content of 12 wt% was satisfactory. However, as shown in Figure 7(B), numerous irregularities were observed on the surface of the blade before coating, suggesting that the coating material provides an anchoring effect.
[0059] Thus, it was confirmed that when a cutting tool is made from a cemented carbide material sintered with WC particles with a particle size of 0.7 μm or less using a binder of 10-16 mass% Co, a strong lubricating coating layer is formed on the cutting tool body, suppressing the occurrence of scalpel scratches due to peeling of the lubricating coating layer, and enabling the production of high-quality, curled sections.
[0060] [Example 2] The blades according to the above embodiment were manufactured with different radius of curvature R and sharpness angle θ at the tip of the blade, and the durability of the lubricating coating layer was tested (life test) by cutting an object. The radius of curvature R at the tip of the cutting edge was varied in 10 nm increments from 10 nm to 50 nm, and the sharpness angle θ was varied in 2 degree increments from 16 degrees to 24 degrees. The cemented carbide had a WC grain size of 0.7 μm and a Co content of 12 wt%. A lifespan test was performed using the same procedure as in Example 1. The results are shown in Table 2.
[0061] [Table 2]
[0062] It was confirmed that the cutting quality reached the target cutting quality when the radius of the blade tip was between 20 nm and 40 nm, and the angle of the blade tip was between 18 and 22 degrees. [Industrial applicability]
[0063] The cutting tool of the present invention can be widely used, in particular, for cutting materials that require precise cutting quality, such as biological specimens. [Explanation of Symbols]
[0064] 1. Blade body 11 Scoop surface 12 Escape 1A base 1B Pointed part 2 Primer particles 3. Top coat particles 10. Cutlery A1 First area A2 Second area A3 Third area C Lubricating coating layer C1 First lubricating coating layer C2 Second lubricating coating layer E. Tip of the blade L1 Primer layer L2 Top Coat Layer R: Radius of curvature of the cutting edge. t Thickness of the blade itself θ: Sharpness angle (angle at the tip of the cutting edge) L Blade length W,W1,W2 width M mark L1 Reference Line V,H reference line
Claims
1. A cutting tool body made of a cemented carbide made of a composite material obtained by sintering metal particles with a particle size of 0.7 μm or less with a binder in an amount of 10% to 16% by mass, comprising a flat base and a pointed portion formed at the tip of the base, wherein at least the surface of the pointed portion has irregularities in which the ground metal particles form convex portions and the binder forms concave portions, At least the pointed portion comprises a lubricating coating layer having a primer layer and a topcoat layer formed by the solidification of a liquid coating material. A bladed weapon.
2. The blade according to claim 1, used as a replacement blade for a microtome.
3. The cutting tool according to claim 1, wherein the thickness of the lubricating coating layer is 10 nm to 30 nm.
4. The cutting tool according to claim 1, characterized in that the radius of curvature of the tip of the pointed portion is 20 nm to 40 nm, and the tip angle of the cutting edge is 18 degrees to 22 degrees.
5. The blade according to any one of claims 1 to 4, wherein the top coat layer is formed of a monolayer.
6. The pointed portion comprises a first region extending from the tip of the cutting edge, including the tip of the cutting edge, and a second region following the first region. The blade according to claim 5, wherein the primer layer of the first region is formed to be thinner than the primer layer of the second region.
7. The blade according to claim 6, wherein the surface roughness of the blade surface in the first region is formed to be smoother than that of the blade surface in the second region.
8. The blade according to any one of claims 1 to 4, wherein the lubricating coating layer comprises a primer layer formed by the solidification of a coating material containing silica fine particles and a top coat layer formed by the solidification of a fluorine-based water-repellent coating material.
9. A method for manufacturing a cutting tool, comprising a cutting tool body made of a cemented carbide made of a composite material obtained by sintering metal particles with a particle size of 0.7 μm or less with 10% to 16% by mass of a binder, the cutting tool body having a flat base and a pointed portion formed at the tip of the base, wherein at least the surface of the pointed portion has irregularities where the ground metal particles are convex and the binder is concave, and a liquid coating material is applied to at least the pointed portion of the cutting tool body and solidified to form a lubricating coating layer comprising a primer layer and a topcoat layer.
Citation Information
Patent Citations
JP1980077464U
The data sheet for the wind motor - - - - carbon ball curtain
JP1985124394U
Sic coating blade for microtome and manufacture thereof
JP1987152626A
Diamond coated sintered hard alloy and its production
JP1988014869A
JP1989087322U